Pharmacokinetics and Immunological Effects of Romidepsin in Rhesus Macaques - Kleinman, Adam J.; Xu, Cuiling; Cottrell, Mackenzie L.; Sivanandham, Ranjit; Brocca-Cofano, Egidio; Dunsmore, Tammy; Kashuba, Angela; Pandrea, Ivona; Apetrei, Cristian (Frontiers in Immunology, 2020)
HIV/SIV persistence in latent reservoirs requires lifelong antiretroviral treatment and calls for effective cure strategies. Romidepsin (RMD), a histone deacetylase inhibitor, was reported to reactivate HIV/SIV from reservoirs in virus-suppressed individuals. We characterized in detail the pharmacokinetics and safety profile of RMD in three SIV-naïve rhesus macaques which received two rounds of treatment. In plasma, RMD mean terminal half-life was 15.3 hours. In comparison, RMD mean terminal half-life was much longer in tissues: 110 hours in the lymph nodes (LNs) and 28 hours in gastrointestinal tract. RMD administration was accompanied by transient liver and systemic toxicity. Isoflurane anesthesia induced near-immediate transient lymphopenia, which was further exacerbated and extended with the extensive immune modifications by RMD. The effect of RMD on circulating immune cells was complex: (i) slight increase in lymphocyte death rates; (ii) transient, robust increase in neutrophils; (iii) massive downregulation of lymphocyte surface markers; (iv) important migration of CD3+ T cells to the gut and LNs; and (v) hindrance to CD8+ T cell functionality, yet without reaching significance. Our results show that, in contrast to transient plasma concentrations, RMD has a long-term presence in tissues, with multiple immunomodulatory effects and minimal to moderate kidney, liver, and lymphocyte toxicities. As such, we concluded that RMD can be used for “shock and kill" approaches, preferentially in combination with other latency reversal agents or cytotoxic T lymphocyte boosting strategies with consideration taken for adverse effects.